THIN-WALLED BARRELL SHELL DEFLECTIVE MODE ANALYSIS (Academic journal Industrial Machine Building Civil Engineering, 2018)
The paper deals with the deflective mode of steel rotary shell with different form of outer surface that are loaded with axially symmetric load. The results show solution of shell voltage and strain equation under the load that is described by exponential law and based on efforts from temperature differentials. Besides, the paper represents design formulas for deflection analysis, running bending moments and running transverse forces in shells with different abutment to the basis. It was shown the basic function of deflection and maximum value of relevant parameters of the reaction. The analysis of aspects about efficiency of using corrugated wall for steel barrel shell is done. The results in analytical and graphical form are shown. According to resulting formulas, it was made comparative calculations of shells with constant and variable wall thickness.
Keywords: barrel shell; exponential law; deflection functions; state of stress; zone of end effect